(untitled) (Foro de Educacion, 2015)
The evaluation of educational policies is a political, scientific and social priority. This is due to the existence of a policy concern for advancing the design and implementation of policy impact, linked with the interest of the scientific community to better understand the meaning and function of education policy in improving the quality of education systems in democratic societies. Therefore, this article reviews the status of the educational policy evaluation so as to allow us to establish: the theoretical perspectives with greater tradition in this arena and the emerging positions, the methodological issues related to the development of systems evaluation indicators and index, and current challenges posed by the movement of Informed-Policy. Thus, it advocates a descriptive-exploratory approach with reference sources and primary data. The results draw: a tendency to establish links between empirical evidence and educational policies in terms of Informed-Policy, and a growing concern for evaluations of Informed-Policy in Education about their contributions to educational equity.